A qualitative, phenomenological study of scabies patients at Cikatomas Health Center - Desy Linasari; Sylvia Mustika Sari; Selly Andriani; Ris kristiana; Henny Juliastuti (ACTA Medical Health Sciences, 2024)
Infestation with the Sarcoptes scabies mite causes scabies, an infectious skin disease that is often found in densely populated areas. This disease is characterized by itching, especially at night, as well as the appearance of rashes and lesions on the skin. Scabies is an endemic public health problem that attacks groups of people with poor personal hygiene. This research aims to understand the experiences of scabies patients regarding their disease journey, including treatment and prevention efforts. The research method used is qualitative with a phenomenological approach. Participants were selected using purposive sampling, and a total of seven participants from Cikatomas Health Center, Tasikmalaya Regency, were included. We collected data through in-depth interviews. From the research results, five themes emerged regarding the experiences of scabies patients in their disease journey: symptoms, risk factors, chain of transmission, treatment efforts, and prevention efforts. In conclusion, during the onset of symptoms, patients reported experiencing intense itching, particularly, in several areas of the body. The most prominent risk factors found in patients were poor personal hygiene and inadequate housing density. The chain of transmission occurred due to contact with other scabies patients, including a history of sharing beds in dormitories and using shared items. Patients sought treatment at health facilities, but did not receive treatment together with friends or other affected family members, thereby allowing the chain of transmission to continue. Prevention efforts have been made by improving personal hygiene. DOI : 10.35990/amhs.v3n1.p12-23 REFERENCES Sungkar S. Skabies: Etiologi, Patogenesis, Pemberantasan dan Pencegahan. Jakarta: Badan Penerbit Fakultas Kedokteran Universitas Indonesia; 2016. Djuanda A, Suriadiredja ASD, Sudharmono A. Ilmu Penyakit Kulit dan Kelamin. Edisi ke-7. Jakarta: Badan Penerbit Fakultas Kedokteran Universitas Indonesia; 2016. Marga P. Pengaruh personal hygiene terhadap kejadian penyakit skabies. J Ilm Kesehatan Sandi Husada. 2020;9(2):773–8. Leung A, Lam J, Leong K. Scabies: A neglected global disease. Curr Pediatr Rev. 2020;16(1):33–42. World Health Organization. Scabies. Geneva: WHO; 2020 [cited 2023 Nov 8]. Available from: https://www.who.int/news-room/fact-sheets/detail/scabies El-Moamly AA. Scabies as part of the WHO roadmap for neglected tropical diseases 2021–2030: What we know and what we need to do for global control. Trop Med Health. 2021;49(1):1–11. Wibianto A, Santoso I. Prevalensi penderita skabies di Puskesmas Ciwidey, Jawa Barat (2015–2020): Studi retrospektif. 2020;1:281–90. Kumarayanti NKD, Hapsari Y, Kusuma DR. Penatalaksanaan skabies dengan pendekatan kedokteran keluarga pada pasien dewasa. J Kedokt. 2020;9(2):220–8. Dinas Kesehatan Jawa Barat. Profil Kesehatan Kabupaten Tasikmalaya 2019. Bandung: Dinkes Jabar; 2019. Available from: https://dinkes.jabarprov.go.id/ Kurniawan M, Sie M, Ling S. Diagnosis dan terapi skabies. Cermin Dunia Kedokteran. 2020;47(2):104–7. Tanto C, Liwang F, Hanifati S. Selekta Kedokteran. Edisi IV Jilid 1. Jakarta: Media Aesculapius; 2016. p. 311–2. Rofifah TN, Budi U. Hubungan sanitasi asrama dan personal hygiene santri dengan kejadian scabies di Pondok Pesantren Al Ikhsan, Banyumas. 2019;38(1):1–23. Suciaty S, Ismail S. Profil penyakit skabies di wilayah kerja Puskesmas Kamonji tahun 2018. Medika Alkhairaat. 2021;3(2):45–50. Naftass Z, Putri TR. Hubungan jenis kelamin, tingkat pendidikan, dan pengetahuan terhadap kejadian skabies pada santri Pondok Pesantren Qotrun Nada, Depok. 2018;10(2):115–9. Muslih R. Hubungan personal hygiene dengan kejadian skabies pada santri Pondok Pesantren Cipasung, Tasikmalaya. Tasikmalaya: Fakultas Ilmu Kesehatan Universitas Siliwangi; 2012. Mutiara H, Syailindra F. Skabies. Med J Lampung Univ (MAJORITY). 2016;5(2):37–42. Handari, Yamin M. Analisis faktor kejadian skabies di Pondok Pesantren An-Nur, Ciseeng, Bogor. J Kedokt dan Kesehatan. 2018;14(2):74–82. Purwanto H, Hastuti RP. Faktor risiko penyakit skabies di masyarakat. J Kesehatan. 2020;11(1):145–50. Mading M, Bule Sopi I. Kajian aspek epidemiologi skabies pada manusia. J Penyakit Bersumber Binatang. 2019;2(2):9–17. Rosumeck S, Nast A, Dressler C. Ivermectin and permethrin for treating scabies (review). Cochrane Library. 2018:60–4. Gunning K, Kiraly B, Pippitt K. Lice and scabies: Treatment update. Am Fam Physician. 2019;99(10):635–42.